2009
DOI: 10.1080/10810730902806810
|View full text |Cite
|
Sign up to set email alerts
|

Health Care System Approaches for Cancer Patient Communication

Abstract: Cancer patient communication is always embedded in a complex background of inter-related parts, i.e., a system. Cancer patients are specifically exposed to a healthcare system. Considering this context, this article summarizes the insight from a roundtable discussion involving behavioral medicine and oncology experts convened at the 2008 Annual Meeting of the Society of Behavioral Medicine as part of an annual pre-conference course entitled "Interpersonal Communication and Cancer Control: Emerging Themes". In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Cancer patients in particular have high information needs, and these might be well-served by interaction with an EHR 14 by, for example, using a patient portal, as discussed below. Even at the level of a single provider and patient, there are opportunities to integrate the EHR more fully into the visit as an enabler of patient-centered care and a communication tool.…”
Section: Informatics-assisted Patient Management To Provide Quality mentioning
confidence: 99%
“…Cancer patients in particular have high information needs, and these might be well-served by interaction with an EHR 14 by, for example, using a patient portal, as discussed below. Even at the level of a single provider and patient, there are opportunities to integrate the EHR more fully into the visit as an enabler of patient-centered care and a communication tool.…”
Section: Informatics-assisted Patient Management To Provide Quality mentioning
confidence: 99%
“…Patient centered communication has been shown to influence the recall of information, treatment adherence, and satisfaction with care and health outcomes [21,70,[109][110][111][112][113]. In a study by Johnson et al, physicians were found to be more verbally dominant, and therefore less 'patient centered' when dealing with African American patients [109].…”
Section: Patient Centered Care -Disparity In Carementioning
confidence: 99%
“…In the US, there are approximately nineteen -million people who have a limited proficiency in English, Studies have shown that language discordance harms healthcare process and lowers the patients' ratings of care [113][114][115][116][117][118][119][120][121][122][123][124][125]. In a study involving Hispanic patients, it was discovered that those proficient in English were more likely to have medication side effects explained to them and have a higher patient satisfaction rating [117].…”
Section: Patient Centered Care -Disparity In Carementioning
confidence: 99%
“…Examples include surgery to remove a tumor, systemic chemotherapy and established psycho‐oncology interventions, such as various psychotherapies, or exercise and diet changes targeting poor coping and distress in cancer survivors. Quaternary prevention refers to highly specialized care which aims to alleviate unnecessary intervention and focus on reducing suffering and optimize comfort, as in palliative medicine . The public health and research goals for the four levels of prevention are presented in Table .…”
Section: Estimated Proportion Of Cancers Attributed To Different Knowmentioning
confidence: 99%
“…1331 Cancer prevention within psycho-oncology reducing suffering and optimize comfort, as in palliative medicine [37]. The public health and research goals for the four levels of prevention are presented in Table 2.…”
mentioning
confidence: 99%